2018
DOI: 10.1038/s41467-018-05090-y
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortex and its input to the basolateral amygdala control innate fear response

Abstract: Prefrontal brain areas are implicated in the control of fear behavior. However, how prefrontal circuits control fear response to innate threat is poorly understood. Here, we show that the anterior cingulate cortex (ACC) and its input to the basolateral nucleus of amygdala (BLA) contribute to innate fear response to a predator odor in mice. Optogenetic inactivation of the ACC enhances freezing response to fox urine without affecting conditioned freezing. Conversely, ACC stimulation robustly inhibits both innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 49 publications
(76 reference statements)
7
83
0
1
Order By: Relevance
“…Recent studies have reported that the amygdala plays a central role in processing innate fear of predator odors and looming visual threats (Jhang et al, 2018;Salay et al, 2018;Wei et al, 2015). We thus tested some of our recorded BLA neurons upon exposure to cat odor, looming objects, as well as loud noises.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported that the amygdala plays a central role in processing innate fear of predator odors and looming visual threats (Jhang et al, 2018;Salay et al, 2018;Wei et al, 2015). We thus tested some of our recorded BLA neurons upon exposure to cat odor, looming objects, as well as loud noises.…”
Section: Resultsmentioning
confidence: 99%
“…Congruent with this idea, a physical therapy study showed that vestibular exercise can improve acrophobia symptoms (Whitney et al, 2005). Another possibility for the reduced responses in the enclosed high place is a regulation by cortical inputs, such as from the anterior cingulate cortex, which plays a role in the inhibition of innate fear (Jhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed for maximal separation of PL and IL but caused spread of the virus into the anterior cingulate (Cg) and dorsal peduncular (DP) cortices in some cases. Recently, the anterior cingulate cortex and its input to the basolateral amygdala has been implicated in mediating innate freezing response to predator odors (Jhang et al, 2018), which is similar to the role the PL plays in learned fears (Corcoran and Quirk, 2007). Although the projection from the dorsal peduncular cortex to the BLA has not been directly characterized, the DP is thought to play a role similar to the IL and is often included when examining conditioned responses such as fear and drug seeking (Peters et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The BLA is critical for fear learning and anxiety-like behavior, but is also implicated in novelty responses (Balderston et al 2011;Jhang et al 2018). LC-NE signaling within the BLA elicits anxiety-like behavior in canonical anxiety tests as well measures of social anxiety (McCall et al 2017;Siuda et al 2016), but the role of the LC-NE à BLA circuit in neophobia has not been described.…”
Section: Ne-deficient Mice Show Reduced C-fos Induction In Select Tarmentioning
confidence: 99%